PENGARUH OUTDOOR EDUCATION TERHADAP PERSONAL & SOCIAL RESPONSIBILITY SERTA KEBUGARAN JASMANI - Rimasa, Dery (2016)
The aim of research to determine the impact of outdoor education activities of the personal & social responsibility and physical fitness. The research method used was Quasi-Experimental design Nonequivalent (pretest and posttest) Control-Group Design. The population of the entire students of grade VIII SMP Pasundan 2 Cimahi, class VIII C selected sample consisting of 40 students, then divided into two groups, the experimental group and the control group. The instrument used was a questionnaire Personal & Social Responsibility and Bleep test. The analysis of the experimental group affect the Personal & Social Responsibility and Physical Fitness. The results of analysis and calculation states that Personal & Social Responsibility experimental group increased an average of 7.25 compared to the control group with an average of 2.35 and improving the physical fitness of the experimental group increased by an average of 1.83 compared with the control group with an average of 0.055. In conclusion, the activity of Outdoor Education has increased the Personal & Social Responsibility and physical fitness of students.;---Tujuan penelitian untuk mengetahui dampak aktivitas Outdoor education terhadap personal & social responsibility serta kebugaran jasmani. Metode penelitian yang di gunakan ialah Quasi-Experimental dengan desain Nonequivalent (Pretest and Posttest) Control-Group Design. Populasi seluruh siswa kelas VIII SMP Pasundan 2 Cimahi, sampel terpilih kelas VIII C yang terdiri dari 40 siswa, kemudian dibagi menjadi dua kelompok yaitu kelompok eksperimen dan kelompok kontrol. Instrument yang digunakan adalah angket Personal & Social Responsibility dan Bleep test. Hasil analisis pada kelompok eksperimen berpengaruh terhadap Personal & Social Responsibility serta Kebugaran Jasmani. Hasil analisis dan perhitungan menyatakan bahwa Personal & Social Responsibility kelompok ekperimen terjadi peningkatan rata-rata 7.25 dibandingkan kelompok kontrol dengan rata-rata 2.35 serta peningkatan kebugaran jasmani kelompok eksperimen meningkat dengan rata-rata 1.83 dibandingkan dengan kelompok kontrol dengan rata-rata 0,055. Kesimpulan, aktivitas Outdoor Education telah meningkatkan Personal & Social Responsibility serta kebugaran jasmani pada siswa